Children's and young people's human rights education in school: Cardinal complications and a middle ground. Issue 4 (8th August 2022) - Quennerstedt, Ann
Abstract: This article examines the academic discussion about human rights education for children and young people and argues that the current state of research does not provide sufficient support and guidance to nations, schools, and teachers in the establishment of human rights education in schools. The article's aim is to add insights into how scholarly work may be contributing to the low uptake of human rights education in formal schooling. By drawing on educational children's rights research and research on human rights education, three cardinal complications are identified; (1) that the main research fields that address education and rights do not seem to communicate, (2) that it is unclear what are the aims of human rights education are, and (3) that a curriculum for human rights education is missing. The cardinal complications are closely examined and discussed, and a middle ground is explored and progressively visualized.